Unveiling Silent Narratives: Deconstructing the Struggles of Inggit Garnasih and Nyi Amsi in the Film Ketika Bung di Ende as a History Learning Media" - Wati, Fatma; Meo, Claudia Moi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study discusses the deconstruction of women's roles representation in the film *Ketika Bung di Ende*, focusing on the characters of Inggit Garnasih and Nyi Amsi. A qualitative approach was employed, using narrative analysis and deconstruction methods. The results reveal that the film successfully portrays women's struggles not only in public spaces but also within the domestic sphere, through resilience, personal sacrifice, and emotional support. Inggit Garnasih and Nyi Amsi are depicted as key figures who sustained Bung Karno’s spirit during his exile. Furthermore, the film proves to be an effective historical learning medium, enriching students' understanding of women's contributions to Indonesia’s independence movement and promoting a more inclusive and humanistic historical awareness.